Regulating unmanned aircraft systems in Antarctica: challenges and collaborative solutions - Yitong Chen; Shu Wu (Frontiers in Marine Science)
The increasing use of unmanned aircraft systems (UAS) globally presents significant opportunities and challenges for Antarctic governance, particularly in terms of operational safety and environmental protection. This study investigates the challenges faced by various stakeholders in regulating UAS operations in Antarctica and identifies collaborative solutions, employing both empirical and comparative research methodologies. Data on domestic UAS regulations and Antarctic-specific rules from Antarctic Treaty Consultative Parties (ATCPs) were obtained through their official civil aviation websites, while the involvement of non-state actors in the Antarctic Treaty Consultative Meeting (ATCM) was assessed using information provided by the Antarctic Treaty Secretariat. The findings reveal that ATCPs have developed guidelines, manuals, and other regulatory tools and contribute actively to ATCM discussions. Non-state actors, leveraging their interdisciplinary expertise and research capabilities, also play a critical role in shaping UAS regulatory frameworks. Nevertheless, current rules governing UAS operations in Antarctica remain fragmented, underscoring the need for a more cohesive and comprehensive regulatory framework. As UAS regulations in Antarctica continue to evolve, effective rulemaking will require collaboration among diverse actors, integrating practical expertise, global regulatory standards, and the unique operational conditions of the Antarctic region. A comprehensive legally binding Measure or at least a resolution adopted by ATCM may be good start for this integrated regulatory process.